Penyuluhan Kesehatan tentang Hipertensi, Pemeriksaan Tekanan Darah, dan Pelaksanaan Senam Hipertensi pada Lansia di Kelurahan Pattan Ulusalu, Kecamatan Ulusalu, Kabupaten Tana Toraja - Hayuti Windha Pagiu; Betriani Disik; Lucia Yogyana Suramas; Nofita Tudang Rombeallo (PPNI UNIMMAN, 2025)
Hypertension is a disease that does not show symptoms or complaints. However, if detected at an advanced stage of the disease, it can result in disability or death. Hypertension is increasing, especially in the elderly group, known as the Silent Killer disease (Ministry of Health, 2019). In Indonesia and in several countries in the world, hypertension has become a major health problem, where the increase in hypertension cases is estimated to increase by around 80%, especially in developing countries in 2025 from 639 million cases in 2000, and is estimated to increase to 1.5 billion cases in 2025 (Hakim L., 2019). Increasing public awareness can be done through promotive and preventive efforts by conducting early detection of routine blood pressure measurements and compliance in taking medication routinely (Astutiatmaja, 2022). The purpose of this community service activity is to increase the knowledge of the elderly about controlling and treating hypertension to prevent the risk of complications of other degenerative diseases due to hypertension and as an evaluation to increase the knowledge of the elderly to maintain health in old age so that complications of the disease can be prevented in improving the quality of life of the elderly